Complement Receptors C5aR and C5L2 Are Associated with Metabolic Profile, Sex Hormones, and Liver Enzymes in Obese Women Pre- and Postbariatric Surgery - Reza Rezvani; Jessica Smith; Marc Lapointe; Picard Marceau; Andre Tchernof; Katherine Cianflone (Hindawi Limited, 2014)
Objective. Obesity is associated with metabolic dysfunction with sex differences and chronic, low-grade inflammation. We proposed that hepatic expression of immune complement C3 related receptors (C3aR, C5aR, and C5L2) would be associated with pre- or postmenopausal status and metabolic profile in severely obese women. We hypothesized that C5L2/C5aR ratio, potentially influencing the ASP/C5L2 metabolic versus C5a/C5aR immune response, would predict metabolic profiles after weight loss surgery. Materials and Methods. Fasting plasma (hormone, lipid, and enzyme analysis) and liver biopsies (RT-PCR gene expression) were obtained from 91 women during surgery. Results. Hepatic C5L2 mRNA expression was elevated in pre- versus postmenopausal women (P<0.01) and correlated positively with circulating estradiol, estrone, ApoB, ApoA1, ApoA1/B, waist circumference, age, and LDL-C (all P<0.05). While plasma ASP was lower in pre- versus postmenopausal women (P<0.01), the hepatic C5L2/C5aR mRNA ratio was increased (P<0.001) and correlated positively with estrone (P<0.01) and estradiol (P<0.001) and negatively with circulating ApoB and liver enzymes ALT, AST, and GGT (all P<0.05). Over 12 months postoperatively, liver enzymes in low C5L2/C5aR mRNA ratio group remained higher (ALP and ALT, P<0.05, AST and GGT, P<0.001 2-way-ANOVA). Conclusion. C5L2-C5aR association with other mediators including estrogens may contribute to hepatic metabolic and inflammatory function.